CUTTING PRICE MENURUT HUKUM ISLAM : (Studi Kasus di Pasar Simpang Tiga) - Azimi, Zul (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
This study aims to determine the impact of cutting prices on businesses and consumers and a review of Islamic law on practice at the grocery wholesale shop in the Simpang Tiga Market. The research method used is a qualitative method to obtain the author's data using the Field Research method, using interviews, observations, and documentation. The study results showed that buying and selling with a cutting-price system conducted by food traders in the Simpang Tiga Market is one of the forms of business competition. The traders do the food price of items aimed at increasing customers and reducing the stock of existing goods. In Islamic law, buying and selling with a cutting-price system is not justified because the practice of cutting prices can kill other people's efforts, so their actions can be classified as wrongdoing against other parties. Cutting prices is caused by a lack of understanding of the religion of the merchant.